Software defined radio frequency sensing framework for intelligent monitoring of sleep apnea syndrome - Khan, Muhammad Bilal; AbuAli, Najah; Hayajneh, Mohammad; Ullah, Farman; Rehman, Mobeen Ur; Chong, Kil To (Methods (San Diego, Calif.), 2023)
•A non-invasive intelligent SDRF sensing framework is developed for diagnosing sleep apnea syndrome using the multi-carrier orthogonal frequency division multiplexing (OFDM) technique to extract the fine-grained WCSI.•Collected a real-time dataset of 25 subjects for 100 experiments with 14,600 records for four breathing patterns using the SDRF sensing in the lab environment.•A feature selection approach is used for feature scoring to reduce the dimensions of the dataset and extract meaningful information.•The machine learning classification models are trained on the dataset of SDRF sensing, and classification performance is evaluated. Healthy sleep is vital to all functions in the body. It improves physical and mental health, strengthens resistance against diseases, and develops strong immunity against metabolism and chronic diseases. However, a sleep disorder can cause the inability to sleep well. Sleep apnea syndrome is a critical breathing disorder that occurs during sleeping when breathing stops suddenly and starts when awake, causing sleep disturbance. If it is not treated timely, it can produce loud snoring and drowsiness or causes more acute health problems such as high blood pressure or heart attack. The accepted standard for diagnosing sleep apnea syndrome is full-night polysomnography. However, its limitations include a high cost and inconvenience. This article aims to develop an intelligent monitoring framework for detecting breathing events based on Software Defined Radio Frequency (SDRF) sensing and verify its feasibility for diagnosing sleep apnea syndrome. We extract the wireless channel state information (WCSI) for breathing motion using channel frequency response (CFR) recorded in time at every instant at the receiver. The proposed approach simplifies the receiver structure with the added functionality of communication and sensing together. Initially, simulations are conducted to test the feasibility of the SDRF sensing design for the simulated wireless channel. Then, a real-time experimental setup is developed in a lab environment to address the challenges of the wireless channel. We conducted 100 experiments to collect the dataset of 25 subjects for four breathing patterns. SDRF sensing system accurately detected breathing events during sleep without subject contact. The developed intelligent framework uses machine learning classifiers to classify sleep apnea syndrome and other breathing patterns with an acceptable accuracy of 95.9%. The developed framework aims to build a non-invasive sensing system to diagnose patients conveniently suffering from sleep apnea syndrome. Furthermore, this framework can easily be further extended for E-health applications.